Model Answer For Critical Review Paper: Conjoint Examination For Malaysian Master Of Medicine (Psychiatry) And Master Of Psychological Medicine May 2013 - Hazura, H; Wan Norhaida, WA; Ruzita, J; Othman, Zahiruddin; Sidi, Hatta; Midin, Marhani (ASEAN Federation of Psychiatry and Mental Health (AFPMH), 2013)
Objective: This paper aims to discuss the answers to a Critical Review Paper used in the Malaysian Master of Medicine (Psychiatry) and Master of Psychological Medicine examination conducted in May 2013. Methods: One part of this broader postgraduate examination is to evaluate the students’ skills of critical appraisal through answering questions based on a journal paper. Results: Model answers were provided at the end of the Critical Review Paper. The objective of the study presented in the review paper was to investigate the association of cigarette smoking with verbal working memory and psychopathology of patients with schizophrenia. Conclusion: This review paper had fairly evaluated the students’ understanding and critical thinking on the given topic. This paper may serve as a guideline to teach students how to critically appraise research papers related to psychiatry.